Persistent cognitive impairment, hippocampal atrophy and EEG changes in sepsis survivors. Issue 1 (7th November 2012) - Semmler, Alexander; Widmann, Catherine Nichols; Okulla, Thorsten; Urbach, Horst; Kaiser, Markus; Widman, Guido; Mormann, Florian; Weide, Julia; Fliessbach, Klaus; Hoeft, Andreas; Jessen, Frank; Putensen, Christian; et al.
Abstract : Objectives: The objective of this preliminary study was to explore long-term changes in neurobehavioral parameters, brain morphology and electroencephalography of sepsis patients who received intensive care compared to non-septic intensive care unit (ICU) patients. Methods: Two-centre follow-up study 6–24 months after discharge from hospital using published norms and existing databases of healthy controls for comparison. Patients included 25 septic and 19 non-septic ICU survivors who were recruited from two ICUs of a university and community hospital. Measurements used include brain morphology, standard electroencephalography, cognition and psychiatric health and health-related quality of life. Results: Sepsis survivors showed cognitive deficits in verbal learning and memory and had a significant reduction of left hippocampal volume compared to healthy controls. Moreover, sepsis and to some extent non-septic ICU patients had more low-frequency activity in the EEG indicating unspecific brain dysfunction. No differences were found in health-related quality of life, psychological functioning or depressive symptoms, and depression could be ruled out as a confounding factor. Conclusions: This study demonstrates permanent cognitive impairment in several domains in both septic and non-septic ICU survivors and unspecific brain dysfunction. In the sepsis group, left-sided hippocampal atrophy was found compared to healthy controls. Further study is needed to clarify what contribution sepsis and other factors at the ICU make to these outcomes. Specific neuroprotective therapies are warranted to prevent persisting brain changes in ICU patients.